Reduced Left Ventricular Ejection Fraction Is a Risk Factor for In-Hospital Mortality in Patients after Percutaneous Coronary Intervention: A Hospital-Based Survey. (5th December 2018) - Ye, Ziliang; Lu, Haili; Li, Lang
Abstract : Background . To evaluate whether a reduced left ventricular ejection fraction (LVEF) is a risk factor in patients after percutaneous coronary intervention (PCI). Methods . A retrospective cohort study from February 2013 to January 2017 was performed, and 1600 patients were included (136 patients with EF <50% and 1464 patients with EF ≥50%); all patients underwent PCI. Revascularization, in-hospital mortality, and in-hospital myocardial infarction (MI) during hospitalization were evaluated. Results . The mean age of patients with EF <50% was 62.18 ± 10.31 years, while the mean age of patients with EF ≥50% was 60.06 ± 10.89 years (P=0.029). In-hospital mortality of patients with EF ≥50% was significantly lower than that of patients with EF <50% (0.12% vs. 3.68%, P<0.001), while no difference was observed in revascularization and in-hospital MI between the two groups (2.39% vs. 2.20%, P=0.892; 0.415% vs. 1.47%, P=0.093, respectively). In the univariate analysis, no significant difference was found in revascularization and in-hospital MI between the two groups (OR: 1.50, 95% CI: 0.95 to 2.38; OR: 0.28, 95% CI: 0.06 to 1.38, respectively) except for in-hospital mortality (OR: 1.12, 95% CI: 1.05 to 1.27). In multivariate analyses, in-hospital mortality of patients with EF ≥50% was still significantly lower than of patients with EF <50% (OR: 1.15, 95% CI: 1.08 to 1.33). There were no differences in revascularization and in-hospital MI between the two groups (OR: 0.85, 95% CI: 0.44 to 1.63; OR: 0.04, 95% CI: 0.00 to 1.84, respectively). Conclusions . Reduced LVEF is a risk factor for in-hospital mortality in patients after PCI.